2000
DOI: 10.1046/j.1365-3059.2000.00458.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection of onion leaves by Alternaria porri and Stemphylium vesicarium and disease development in controlled environments

Abstract: Infection of onion by Alternaria porri and Stemphylium vesicarium was investigated under a range of controlled temperatures (4±258C) and leaf wetness periods (0±24 h). Conidia of A. porri and S. vesicarium germinated within 2 h when incubated at 48C. Terminal and intercalary appressoria were produced at similar frequencies at or above 108C. The maximum number of appressoria was produced after 24 h at 258C. Penetration of leaves by both pathogens was via the epidermis and stomata, but the frequency of stomatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 18 publications
5
28
0
7
Order By: Relevance
“…The disease was thus rapidly increased in terms of PDI values. The results are also corroborated with the earlier work of Suheri and Price (2000) and Razdan et al, (2008). Severity of the blight depends on the favourable in environmental factor, availability of inoculums and stage of plant growth and time of disease appearance The disease incidence in general continued to increase day by day which might directly be correlated with the epidemiological parameters as there were a subsequent increase in highest relative humidity (RH I), lowest relative humidity (RH II) and rainfall (Table 3).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The disease was thus rapidly increased in terms of PDI values. The results are also corroborated with the earlier work of Suheri and Price (2000) and Razdan et al, (2008). Severity of the blight depends on the favourable in environmental factor, availability of inoculums and stage of plant growth and time of disease appearance The disease incidence in general continued to increase day by day which might directly be correlated with the epidemiological parameters as there were a subsequent increase in highest relative humidity (RH I), lowest relative humidity (RH II) and rainfall (Table 3).…”
Section: Resultssupporting
confidence: 92%
“…Muktakeshi and BCC-1 are the tolerant cultivars, which showed low PDI at suitable epidemiological environment. Razdan et al, (2008) and Suheri and Price (2000) results are agreed with the earlier work.…”
Section: Resultssupporting
confidence: 89%
“…The results of the present study are in conformity with Jakhar et al (1996) who reported that the disease caused by Stemphylium first increased gradually, and then decreased late in the season. The results of the present study revealed that the symptoms of A. porri and S. vesicarium were indistinguishable in the field, which is in conformity with the results of Suheri and Price (2000) who reported that typical purple blotch lesions in the field were often colonized by both the pathogens. Aveling et al, (1993) showed that S. vesicarium, in conjunction with A. porri, was a destructive foliar and seed stalk pathogen of onion under warm, moist conditions.…”
Section: 25supporting
confidence: 92%
“…Dennis (leaf rot or blast), and Stemphylium botroysum. Suheri and Price (2000) reported that both A. porri and S. vesicarium were potentially important pathogens of winter grown Allium crops and purple leaf blotch symptoms were considered to be a complex caused by both the pathogens. Stemphylium botryosum (Pleospora herbarum), S. vesicarium and Alternaria alternata were isolatedin 93.7, 12.5 and 50.0 per cent of the samples, respectively (Cova and Rodriguez, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Stemphylium vesicarium and A. porri are the pathogens most frequently reported on the diseased leaves of garlic. These two pathogens can both cause white or purple spots of onion, and both can be present in the same spots and cause the same level of disease on onion (Suheri and Price 2000b).…”
Section: Introductionmentioning
confidence: 99%